Suitability of the German version of the Manchester Triage System to redirect emergency department patients to general practitioner care: a prospective cohort study. Issue 5 (6th May 2019) - Slagman, Anna; Greiner, Felix; Searle, Julia; Harriss, Linton; Thompson, Fintan; Frick, Johann; Bolanaki, Myrto; Lindner, Tobias; Möckel, Martin
Abstract : Objectives: To investigate the suitability of the German version of the Manchester Triage System (MTS) as a potential tool to redirect emergency department (ED) patients to general practitioner care. Such tools are currently being discussed in the context of reorganisation of emergency care in Germany. Design: Prospective cohort study. Setting: Single centre University Hospital Emergency Department. Participants: Adult, non-surgical ED patients. Exposure: A non-urgent triage category was defined as a green or blue triage category according to the German version of the MTS. Primary and secondary outcome measures: Surrogate parameters for short-term risk (admission rate, diagnoses, length of hospital stay, admission to the intensive care unit, in-hospital and 30-day mortality) and long-term risk (1-year mortality). Results: A total of 1122 people presenting to the ED participated in the study. Of these, 31.9% (n=358) received a non-urgent triage category and 68.1% (n=764) were urgent. Compared with non-urgent ED presentations, those with an urgent triage category were older (median age 60 vs 56 years, p=0.001), were more likely to require hospital admission (47.8% vs 29.6%) and had higher in-hospital mortality (1.6% vs 0.8%). There was no significant difference observed between non-urgent and urgent triage categories for 30-day mortality (1.2% [n=4] vs 2.2% [n=15]; p=0.285) or for 1-year mortality (7.9% [n=26] vs 10.5% [n=72]; p=0.190). Urgency was not a significant predictor of 1-year mortality in univariate (HR=1.35; 95% CI 0.87 to 2.12; p=0.185) and multivariate regression analyses (HR=1.20; 95% CI 0.77 to 1.89; p=0.420). Conclusions: The results of this study suggest the German MTS is unsuitable to safely identify patients for redirection to non-ED based GP care. Trial registration number: U1111-1119-7564; Post-results